Antipsychotic prescribing choices in patients with First Episode Psychosis - J. Fallon; O. Tierney (European Psychiatry, 2022)
Introduction As all first line options in treating First Episode Psychosis (FEP) are similarly effective there is a consensus among prescribing guidelines that clinicians and patients should consider side-effect profile as the ‘driver’ of initial choice of antipsychotic. Anecdotally it has been observed that different care teams prescribe particular medications preferentially.